Impact of payment model on the behaviour of specialist physicians: A systematic review. Issue 4 (April 2020) - Quinn, Amity E.; Trachtenberg, Aaron J.; McBrien, Kerry A.; Ogundeji, Yewande; Souri, Sepideh; Manns, Liam; Rennert-May, Elissa; Ronksley, Paul; Au, Flora; Arora, Nikita; Hemmelgarn, Brenda; Tonelli, Marcello; et al.
Highlights: Physician payment is perceived as an important strategy for improving the value of health care. Evidence on the effects of physician payment is predominantly from primary care. This systematic review synthesizes evidence on specialist physician payment. Payment model affects utilization, but specialists do not always respond to incentives as expected. The specialist payment policy evidence base is limited. Abstract: Physician payment models are perceived to be an important strategy for improving health, access, quality, and the value of health care. Evidence is predominantly from primary care, and little is known regarding whether specialists respond similarly. We conducted a systematic review to synthesize evidence on the impact of specialist physician payment models across the domains of health care quality; clinical outcomes; utilization, access, and costs; and patient and physician satisfaction. We searched Medline, Embase, and six other databases from their inception through October 2018. Eligible articles addressed specialist physicians, payment models, outcomes of interest, and used an experimental or quasi-experimental design. Of 11, 648 studies reviewed for eligibility, 11 articles reporting on seven payment reforms were included. Fee-for-service (FFS) was associated with increased desired utilization and fewer adverse outcomes (in the case of hemodialysis patients) and better access to care (in the case of emergency department services). Replacing FFS with capitation and salary models led to fewer elective surgical procedures (cataracts and tubal ligations) and, with an episode-based model, appeared to increase the use of less costly resources. Four of the seven reforms met their goals but many had unintended consequences. Payment model appears to affect utilization of specialty care, although the association with other outcomes is unclear due to mixed results or lack of evidence. Studies of salary and salary-based reforms point to specialists responding to some incentives differently than theory would predict. Additional research is warranted to improve the evidence driving specialist payment policy.